Elementy logistyki w organizacji imprez sportowych na przykładzie Tour de Pologne - Witkowski, Kazimierz; Cieśliński, Wojciech; Murdza, Krzysztof (Logistics Aspects of Tour De Pologne Organization, 2005)
The paper presents the model of the logistic system applied in the Tour de Pologne. The aim of the research is indication, by means of contrastive analysis, of similarities and specific features of the logistic system structure used for organizing great sport festivities in compare to business logistics of enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 344-352